2014
DOI: 10.2478/s13382-014-0222-7
|View full text |Cite
|
Sign up to set email alerts
|

Plasma thyroid hormones and corticosterone levels in blood of chicken embryos and post hatch chickens exposed during incubation to 1800 MHz electromagnetic field

Abstract: Introduction: This study attempted to determine the effect of a 1800 MHz electromagnetic field (EMF) (only carrier frequency) on thyroxine (T 4 ), triiodothyronine (T 3 ) and corticosterone (CORT) concentrations in the blood plasma of chick embryos, and to investigate the effect of electromagnetic field (EMF) exposure during embryogenesis on the level of these hormones in birds that are ready for slaughter. Material and Methods: Throughout the incubation period, embryos from the experimental group were exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 29 publications
2
17
0
2
Order By: Relevance
“…Although, in this study, the testosterone/follicular-stimulating hormone (FSH) concentration was determined, one important finding, thinning of germinal epithelium (Figure 1(b)), was also reported by other workers, which demonstrated altered testosterone and FSH levels upon RFR exposure (Ozguner et al, 2005;Sarookhani et al, 2011;Wang et al, 2003). The adverse effect of mobile phones on thyroid axis function has been reported previously in rodent models (Eşmekaya et al, 2010;Sinha, 2008), which could act as a double edged sword one-way inhibiting FSH and testosterone production (Jin et al, 2013;Pawlak et al, 2014) and the other way, downregulating sertoli cell (Chandra et al, 2013) and Leydig cell (Mendis-Handagama and Hence, the possibility that RFR interfers with the endocrine regulation of spermatogenesis thereby affecting sertoli cell function could not be ruled out.…”
Section: Discussionmentioning
confidence: 98%
“…Although, in this study, the testosterone/follicular-stimulating hormone (FSH) concentration was determined, one important finding, thinning of germinal epithelium (Figure 1(b)), was also reported by other workers, which demonstrated altered testosterone and FSH levels upon RFR exposure (Ozguner et al, 2005;Sarookhani et al, 2011;Wang et al, 2003). The adverse effect of mobile phones on thyroid axis function has been reported previously in rodent models (Eşmekaya et al, 2010;Sinha, 2008), which could act as a double edged sword one-way inhibiting FSH and testosterone production (Jin et al, 2013;Pawlak et al, 2014) and the other way, downregulating sertoli cell (Chandra et al, 2013) and Leydig cell (Mendis-Handagama and Hence, the possibility that RFR interfers with the endocrine regulation of spermatogenesis thereby affecting sertoli cell function could not be ruled out.…”
Section: Discussionmentioning
confidence: 98%
“…fraction not bound to blood carrier proteins) were analyzed on E18. This is three days before anticipated hatching and at a stage of development when the thyroid hormone levels are sharply rising 35,38 . Both fT3 and fT4 were significantly reduced by the highest dose of the PFAA mixture (3 µg/g egg) compared to the vehicle control.…”
Section: Discussionmentioning
confidence: 99%
“…In any case, this deserves special attention and a detailed comparative study. Although direct effect of RF‐EMF exposure on melatonin has not been confirmed, several studies in the literature reported a potential protective effect of melatonin against the adverse effects induced by RF‐EMF exposure, such as oxidative stress [Kerman et al, 2005; Ozguner et al, 2005a; Köylü et al, 2006; Ozguner et al, 2006; Sokolovic et al, 2008; Kesari et al, 2012; Naziroğlu et al, 2012; Aynali et al, 2013; Sokolovic et al, 2013; Meena et al, 2014; Oksay et al, 2014; Tök et al, 2014; Djordjevic et al, 2015; Sokolovic et al, 2015; Gumral et al, 2016; Pandey and Giri 2018], DNA damage [Lai and Singh, 1997; Liu et al, 2013; Sokolovic et al, 2015; Pandey and Giri, 2018], neuroprotective effects [Erdem Koc et al, 2016], histopathologic changes in skin [Ayata et al, 2004; Ozguner et al, 2004), and adverse effects of EMF on the kidneys [Oktem et al, 2005; Ozguner et al, 2005b; Ulubay et al, 2015] or liver [Gökcimen et al, 2002]. Even though melatonin secretion is not affected by RF‐EMF exposure, it seems to play an important role in the protection of the organism from oxidative stress induced by RF‐EMF exposure.…”
Section: Discussionmentioning
confidence: 99%